PELAKSANAAN PENGAWASAN TERHADAP PEJABAT PEMBUAT AKTA TANAH OLEH KEPALA KANTOR PERTANAHAN KOTA PADANG - Septriana, Silvia (UNES Law Review, 2021)
The Head of the Land Office supervises PPAT as stipulated in the provisions of the Regulation of the Minister of Agrarian affairs and Spatial Planning / Head of the National Land Agency of the Republic of Indonesia Number 2 Year 2018 concerning the Development and Supervision of Land Deed Officials, article 65 of the Regulation of the Head of the National Land Agency No. 1 of 2006 concerning the implementation provisions of Government Regulation No. 37 of 1998 concerning Land Deed Officials. However, in the practice of PPAT carrying out the task is in accordance with the rules or not in accordance with the rules that have been determined the application of the regulation that is not in accordance with the conditions of the field, because the sanctions have not been enforced so that violations occur, one of which is the unreported monthly report of PPAT to the Head of Padang City Land Office.